The study of Broga Hill as an outdoor recreational area in Selangor - Zulkeflee, Farhana; Hj. Baharuddin, Zainul Mukrim (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2017)
Broga Hill is well known as a famous hill for outdoor recreational activities. The hill is fully surrounded by visitors from all over Malaysia especially during weekends and public holidays. Moreover, the hill provides a serene view of Semenyih town from the top of the hill which is fully covered with abandoned wild cogon grass. However, Broga Hill is still having some issues in regard to its physical characters and facilities in that area. This is happening due to the increase in the number of visitors of Broga Hill that could disturb the natural environment as well as low level of safety features provided for visitors. Hence, the aim of this research is to recommend Broga Hill as a good outdoor recreational area for the users in Selangor. In order to achieve the aim of this study, several objectives have been listed to guide the research process such as to study Broga Hill in terms of its physical characters, to identify the related outdoor recreational activities and to come out with recommendations for a better design of the outdoor recreational area. Thus, qualitative and quantitative data have been gathered through the method of documentation analysis, direct observation and survey questionnaires. There are 30 respondents who have participated in the survey. From the findings, this study has identified that Broga Hill is lacking in terms of providing safety features for its visitors and the visitors also did not realised that there are possibilities that they are disturbing the natural environment literally. For that reasons, the recommendations have proposed better and well-functioned facilities that could increase the level of safety for the visitors and save the natural environment surrounding Broga Hill.